Competing values and mediating effects of knowledge chain on organisational performance: A study of service firms in Iran / Amir Hossein Dastaviz - Dastaviz, Amir Hossein (2014)
This thesis aims at examining the impact of competing values on management activities, organizational activities, and organizational performance using the knowledge chain model. Using a random sample set of 302 Iranian service sector firms and a knowledge chain framework, which was adapted and expanded based on structural equation modelling, this thesis examined seven hypotheses on the influence of competing values, and management and organizational activities on organizational performance, including the mediating effects of management activities and organizational activities, on organizational performance. Iran was chosen because of a lack of such research on the developing countries, but especially on countries engulfed by political instability and economic uncertainty. The results produced important analytical conclusions. Firstly, the results show that, adhocracy value enjoyed a direct impact on management activities. Secondly, the results support a significant relationship between competing values and organisational activities of the knowledge chain. Thirdly, despite the presence of a significant relationship between adhocracy and hierarchy values, and organisational performance, a similar relationship did not exist between clan and market values, and organisational performance. Nevertheless, the results show a strong influence of competing values on organisational performance. These results are consistent with past findings. Although the results confirm a significant relationship between management activities and organisational performance, it was not enough to support the effect of organisational activities on organisational performance. Also the contradictory findings on the relationship between adhocracy and knowledge management suggests that it depends on the organisation. Overall, the results show that the knowledge chain model is an influential factor on organisational performance. In addition, the results also show that management III activities have a mediating effect on the relationship between competing values and organisational performance, and the mediating effect of knowledge chain model on the relationship between competing values and organisational performance. In addition, the results show that management activities have a positive impact on the relationship between organizational activities and organizational performance, and on the relationship between organisational activity and knowledge chain model suggesting that organizational performance can be improved by strengthening management activities. Finally, the results also showed the positive effect of the knowledge chain model on the relationship between competing values and organisational performance.